Problem solving technique based on trisilas culture to improve self- regulated learning (SRL) for students in the digital era - Komara, Indra Bangkit; Hartanto, Dody; Barida, Muya; Santosa, Hardi; Saputra, Wahyu Nanda Eka (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Easy internet access is an opportunity for students to obtain various information. Fast digital information that is not balanced with Self-Regulated Learning (SRL) is a serious problem for students. This research aims to determine the effectiveness of problem solving techniques based on Trisilas culture to improve SRL in students. Trisilas is a Sundanese cultural philosophy that is used as a value in social life. The technique problem solving based on trisilas culture consisting of silih asah, silih asih, silih asuh in learning. The method used in this research is a quantitative experiment by examining whether there is an effect of group guidance on problem solving techniques based on trisilas culture on students' SRL. The experimental design used was a non-equivalent control-group design. The instrument in this research used a Scale of Self-Regulated Learning (SSRL). The results of the research showed that after the intervention of group guidance on problem solving techniques based on Trisilas culture, there was an increase of 16.75% in the level of SRL in students. According to the results of the independent sample t test, there is a difference in SRL after or before the intervention, with a 2-tailed significance value of 0.002 <0.05. Currently, there are not many studies that utilize problem- solving techniques based on Trisilas culture in guidance and counseling. The conclusion of this research is that Trisilas culture is a new alternative solution in improving SRL and shows that group guidance on problem solving techniques based on Trisilas culture is effective in making a significant contribution to increasing SRL in students in the digital era.